The kinked demand curve and price rigidity: evidence from scanner data - Maarten Dossche; Freddy Heylen; Dirk Van den Poel (National Bank of Belgium, 2006)
This paper uses scanner data from a large euro area retailer. We extend Deaton and Muellbauer's Almost Ideal Demand System to estimate the price elasticity and curvature of demand for a wide range of products. Our results support the introduction of a kinked (concave) demand curve in general equilibrium macro models. We find that the price elasticity of demand is on average higher for price increases than for price decreases. However, the degree of curvature in demand is much lower than is currently imposed. Moreover, for a significant fraction of products we observe a convex demand curve. We find no correlation between the estimated price elasticity/curvature and the observed size or frequency of price adjustment in our data
Keywords: C33; D12; E3; 330; price setting; real rigidity; kinked demand curve; behavioral AIDS; Preisrigidität; Preiselastizität; Preis-Absatz-Funktion; Gleichgewichtstheorie; Lebensmitteleinzelhandel; Schätzung; EU-Staaten